Disseminated tuberculosis in a Nigerian child: making a case for active contact tracing - Ijezie, Echey; Essien, Ruth Ekomobong; Ijezie, Augustina Elochukwu (International Journal Of Community Medicine And Public Health, 2017)
Tuberculosis (TB) is a significant public health problem globally, especially in developing countries. Every day, up to 200 children (aged less than 15 years) lose their lives to tuberculosis – a preventable and curable disease. Disseminated TB is a potentially life-threatening form of TB, and it is common in infants and children. Contact tracing and the examination of household contacts, particularly of known sputum smear-positive cases, is highly effective in tuberculosis control. Unfortunately, in many high-burden countries, little effort is directed towards identifying contacts of newly diagnosed TB patients. Indeed, TB contact investigations are rarely and inconsistently carried out in resource-limited settings. This failure places children at significant risk. A case of disseminated TB in a child is herein reported, aiming to highlight the pertinent aspects of the history, clinical presentation and outcome, which ultimately underscore the need for active contact tracing. Contact tracing must be strongly advocated for, as this will go a very long way in reducing the burden of childhood TB.